South Africa awaits a possible new law banning foreign ownership and restricting domestic ownership of agricultural land: Is this in line with this country's obligations and commitments under the GATS and its BITS? - Ewers, Jade Güdron (Department of Commercial Law, 2017)
The South African Government publicly announced its intention to table the Regulation of Land Holdings Bill in Parliament soon, as part of their land reform priority. This potential new law aims to prohibit foreign ownership of agricultural land and to place ceilings on the size of agricultural land that citizens and foreigners may own. Foreigners will be allowed to conclude long term leases. Some parties most likely to be affected by this proposed new Bill are South Africa's fellow WTO Members in services trade and investors from its BIT partner countries. As a WTO Member and BIT partner, SA undertook various contractual obligations and commitments. The primary objective of this study is therefore to determine whether, by promulgating the proposed Bill, South Africa might be violating any of these obligations or commitments. This is done by considering firstly the policy and constitutional background of the Bill in light of the General and Specific GATS commitments such as the MFN, Transparency, National Treatment and Market Access Commitments. The outcome of this analysis shows that South Africa may violate its National Treatment and Market Access Specific Commitments by imposing the ban on foreign ownership of agricultural land. This is because those foreign services providers intending to own (as opposed to leasing) agricultural land to establish commercial presence in South Africa, will be prohibited from doing so - despite South Africa's GATS Schedule of Specific Commitments not indicating any such land ownership restrictions either horizontally or sector-specifically. Examples of affected service sectors are the Tourism, Manufacturing and Construction sectors. It is then concluded that (i) South Africa could potentially raise the public order General Exception against any possible violation claims; but (ii) that South Africa should in the alternative, rather consider modifying or withdrawing some of its GATS Commitments. The protections which South Africa's BITs provide are then analysed in light of what is publicly known about the proposed Bill. It is concluded, for example, that the restriction of the property rights of existing foreign owners of agricultural land in South Africa by restricting their rights to dispose of their land to South Africans only – may constitute indirect expropriation for which they should be compensated in terms of relevant BITs. Although the country's investment policy vis a vis BIT has changed leading to the termination of, for example, some European-South African BITs, these agreements all contain sunset clauses opening up the country for potential investor-state arbitration claims for up to 20 years. The thesis concludes with the recommendation that South Africa carefully considers the implications of potential claims from its WTO and BIT partners and in also, other alternative land reform options.